Estimating the impact of co-investment on fiber to the home coverage, adoption and competition - Louise Aimene; Marc Lebourges; Julienne Liang (International Telecommunications Society (ITS), 2019)
Does co-investment enhance fiber to the home (FTTH) coverage, adoption and competition? We combine several French municipality-level datasets and use a two-stage control-function approach to answer this question. In the first stage, we estimate an equilibrium model of entry that predicts the number of FTTH investors in a municipality. In the second stage, we insert the correction term derived from the entry model in the FTTH coverage (adoption, competition) regression to correct for endogeneity of investor entry. The two stages make two contributions. First, we find some FTTH demand and cost factors, which are significant determinants of investor entry. Second, we show that the presence of co-investors does not impact coverage dynamics at the municipality-level, which appears to be determined by French regulatory coverage obligations, i.e., full coverage in five years. In addition, we observe that the presence of co-investment, leads to an increase of 7.6% in FTTH adoption during the 2015-2018 study period and also a more intense competition as shown through the decrease in Orange total retail broadband market penetration by 7.8% for Orange, which is the incumbent operator in France. Our findings confirm that co-investment supports the policy objectives of adoption and competition and should be supported by regulation.
Keywords: L43; L51; L96; 330; Entry model; FTTH coverage; FTTH adoption; competition; co-investment